O PAPEL DA FISIOTERAPIA NO PROGRAMA DE ATENÇÃO AO IDOSO - Pillatt, Ana P.; Berlezi, Evelise M.; Eickhoff, Heloisa M.; Oliveira, Karla R. d.; Huth, Adriane; Bonfada, Sônia T.; Bueno, Cristiane (Salão do Conhecimento, 2013)
Resumo